POSSIBLE INDICATORS OF THE OBSTETRIC ASSISTANCE FOR THE PARTURIENT WOMAN IN A MATERNITY SCHOOL - Mariana da Silva de Figueiredo; Dayanne Kallyne Morais de Araújo Oliveira; Natália Raiane Silva Vieira; Rejane Marie Barbosa Davim; Richardson Augusto Rosendo da Silva (Universidade Federal do Paraná, 2013)
This quantitative descriptive research was undertaken in a maternity school in the city of Natal in the state of Rio Grande do Norte, Brazil. and aimed to characterize the obstetric assistance given to the parturient woman through indicators such as: type of birth, the presence of the companion during the labor, the presence of the companion in the delivery room, breastfeeding in the delivery room, being taken to the shared accommodation, embracement, privacy and physical structure. The sample was made up of 351 women at 12 hours post-partum, and the research was approved and respected ethical precepts. As a result, it was verified that the majority of the parturient women were young, between 20 and 30 years old (56%), that cesarean births predominated (65%) as did the absence of the companions in the delivery rooms (76%). It is concluded that it is necessary to respect the specific legislation, offering the women comprehensive health care, privacy, comfort, embracement and active and resolutive listening.